Comparative Cost Analysis of Housing and Case Management Program for Chronically Ill Homeless Adults Compared to Usual Care - Basu, Anirban (Blackwell Science Inc, 2012)
OBJECTIVE: To assess the costs of a housing and case management program in a novel sample—homeless adults with chronic medical illnesses. DATA SOURCE: The study used data from multiple sources: (1) electronic medical records for hospital, emergency room, and ambulatory medical and mental health visits; (2) institutional and regional databases for days in respite centers, jails, or prisons; and (3) interviews for days in nursing homes, shelters, substance abuse treatment centers, and case manager visits. Total costs were estimated using unit costs for each service. STUDY DESIGN: Randomized controlled trial of 407 homeless adults with chronic medical illnesses enrolled at two hospitals in Chicago, Illinois, and followed for 18 months. PRINCIPAL FINDINGS: Compared to usual care, the intervention group generated an average annual cost savings of (−)$6,307 per person (95 percent CI: −16,616, 4,002; p = .23). Subgroup analyses of chronically homeless and those with HIV showed higher per person, annual cost savings of (−)$9,809 and (−)$6,622, respectively. Results were robust to sensitivity analysis using unit costs. CONCLUSION: The findings of this comprehensive, comparative cost analyses demonstrated an important average annual savings, though in this underpowered study these savings did not achieve statistical significance.